Preclinical evidence for anaplastic lymphoma kinase inhibitors as novel therapeutic treatments for cholangiocarcinoma - Myint, Kyaw Zwar; Sueca-Comes, Mireia; Collier, Pamela; Balasubramanian, Brinda; Venkatraman, Simran; Gordan, John; Zaitoun, Abed M.; Mukherjee, Abhik; Arora, Arvind; Larbcharoensub, Noppadol; Suriyonplengsaeng, Chinnawut; Wongprasert, Kanokpan; et al. (Frontiers in Oncology, 2023)
Introduction Bile duct cancer (cholangiocarcinoma, CCA) has a poor prognosis for patients, and despite recent advances in targeted therapies for other cancer types, it is still treated with standard chemotherapy. Anaplastic lymphoma kinase (ALK) has been shown to be a primary driver of disease progression in lung cancer, and ALK inhibitors are effective therapeutics in aberrant ALK-expressing tumors. Aberrant ALK expression has been documented in CCA, but the use of ALK inhibitors has not been investigated. Using CCA cell lines and close-to-patient primary cholangiocarcinoma cells, we investigated the potential for ALK inhibitors in CCA. Methods ALK, cMET, and ROS1 expression was determined in CCA patient tissue by immunohistochemistry and digital droplet polymerase chain reaction, and that in cell lines was determined by immunoblot and immunofluorescence. The effect on cell viability and mechanism of action of ALK, cMet, and ROS1 inhibitors was determined in CCA cell lines. To determine whether ceritinib could affect primary CCA cells, tissue was taken from four patients with biliary tract cancer, without ALK rearrangement, mutation, or overexpression, and grown in three-dimensional tumor growth assays in the presence or absence of humanized mesenchymal cells. Results ALK and cMet but not ROS were both upregulated in CCA tissues and cell lines. Cell survival was inhibited by crizotinib, a c-met/ALK/ROS inhibitor. To determine the mechanism of this effect, we tested c-Met-specific and ALK/ROS-specific inhibitors, capmatinib and ceritinib, respectively. Whereas capmatinib did not affect cell survival, ceritinib dose-dependently inhibited survival in all cell lines, with IC50 ranging from 1 to 9 µM and co-treatments with gemcitabine and cisplatin further sensitized cells, with IC50 ranging from IC50 0.60 to 2.32 µM. Ceritinib did not inhibit cMet phosphorylation but did inhibit ALK phosphorylation. ALK was not mutated in any of these cell lines. Only ceritinib inhibited 3D growth of all four patient samples below mean peak serum concentration, in the presence and absence of mesenchymal cells, whereas crizotinib and capmatinib failed to do this. Ceritinib appeared to exert its effect more through autophagy than apoptosis. Discussion These results indicate that ceritinib or other ALK/ROS inhibitors could be therapeutically useful in cholangiocarcinoma even in the absence of aberrant ALK/ROS1 expression.